Development of a laboratorial robotized filament winding equipment - Barros, B. (2014)
Filament winding is the mostly suitable technology to produce at large volume scale structural composite parts presenting revolution form, such as pressure and non-pressure vessels, tanks and pipes, aircraft fuselage, helicopter blades, etc. [1, 2]. Such process allows optimising the deposition and orientation of continuous reinforced fibres in order to manufacture the best performance and customised composite part for each specific application. Another advantage of this technological processing method is the possibility it gives of using almost all continuous reinforcing fibres (carbon, glass, aramid) and plastic matrices (both thermosetting and/or thermoplastic). As the investment for acquiring a filament winding equipment was too much high, the Pole for Innovation in Polymer Engineering (PIEP) decided to use its proper know-how to self-develop an own robotised filament winding equipment for laboratorial use. The aim of such equipment is to support R&D projects with industrial companies concerning the production of filament wound scaled prototype parts for testing, optimising and improving fibre deposition trajectories, study the complex shape manufacturing, testing the application of new fibres and matrices, etc. This paper will present the developed and built robotised filament winding equipment and will discuss its major possibilities, trajectories and software data acquisition capabilities and the results obtained on composite parts manufactured by it.